Development Local Culture Story Book to Teach Reading Comprehension for Junior High School - Enggar Wahyu Muji Saputri; Widiarini Widiarini; Istina Atul Makrifah; Tyas Alhim Mubarok (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
This research was used to develop a local culture story book to teach reading comprehension for grade 8 at SMPI Hasanuddin Kesamben Blitar. The subjects used in this study were 20 8th grade students. Based on the results of the needs analysis, it was found that 100% of students' answers did not have any special books that support their learning apart from materials from the government. Furthermore, based on these findings, the research developed a local culture storybook to teach reading comprehension for eighth graders at SMPI Hasanudin Kesamben. The method used in this study was adopted from Borg and Gall by taking some steps that includes: (1) observation and data collection, (2) Planning , (3) Product Development, (4) Validation the Product, (5) Revision stage I, (6) Trials Product, (7) Revision Stage II, (8) Product Improvement. In this study, there are two kinds of validation used to assess the product. The first validation is a material expert who got the result of 80%, its mean that the product is valid category. The second, the validation of media experts got the results of 83,75%, meaning that the product is valid. After the product was validated, then the product was tested on students and obtained student satisfaction responses with the total of 90% which was categorized that the product was Good/Valid.